2021
DOI: 10.1021/acs.macromol.1c01036
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Tacticity on the Crystal Structures of Hydrogenated Ring-Opened Poly(norbornene)s

Abstract: The crystal structures of highly crystalline isotactic and syndiotactic hydrogenated poly(norbornene)s [Hpoly(NB)s], synthesized by the stereospecific ring-opening metathesis polymerizations of norbornene followed by complete hydrogenation, have been determined for the first time on the basis of the X-ray diffraction data analyses. The similarity and difference of the chain conformation and the chain packing mode in the crystal lattice have been clarified among the three kinds of H-poly(NB) samples (syndiotact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 30 publications
1
28
0
Order By: Relevance
“…5 shows the powder XRD patterns of the three copolymers compared with the homopolymers, amorphous H-poly( endo -MNBL) (Fig. 5a) and crystalline H-poly(NB) 32 (Fig. 5e), which shows 2 θ peak tops at 15.8 and 18.4, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…5 shows the powder XRD patterns of the three copolymers compared with the homopolymers, amorphous H-poly( endo -MNBL) (Fig. 5a) and crystalline H-poly(NB) 32 (Fig. 5e), which shows 2 θ peak tops at 15.8 and 18.4, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, changing the tacticity of polymerizing monomer by controlling the C=C bond stereochemistry or by using robust initiators were favorable measures of preventing pDCPD oxidation 36 , 62 . So far, hydrogenation was successful in enhancing the oxidation resistance of, for example, low-crosslinked pDCPD aerogels 63 and ROMP-mediated norbornene polymers 64 . This effect was corroborated by a recent study by Y. Nakama et al 64 from which a strong correlation between oxidation resistance and the changes induced to the chain conformations or packing modes in crystal lattices was confirmed by the wide-angle x-ray diffraction measurement.…”
Section: Resultsmentioning
confidence: 99%
“…So far, hydrogenation was successful in enhancing the oxidation resistance of, for example, low-crosslinked pDCPD aerogels 63 and ROMP-mediated norbornene polymers 64 . This effect was corroborated by a recent study by Y. Nakama et al 64 from which a strong correlation between oxidation resistance and the changes induced to the chain conformations or packing modes in crystal lattices was confirmed by the wide-angle x-ray diffraction measurement. Based on these findings, our group sought to investigate the nanoscale effect of ACs to the development of the DCPD/AC foam crystal structures.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, novel polyolefins, stereoregular hydrogenated polynorbornene (hPNB)­s, in addition to an existing stereoirregular one, , were successfully synthesized via stereoselective ring-opening polymerization. Interestingly, all s -, i -, and atactic ( a )-hPNBs crystallize in monoclinic ( a = 5.97 Å, b = 9.48 Å, c = 12.58 Å, and β = 60°), orthorhombic ( a = 5.95 Å, b = 8.25 Å, c = 12.65 Å), and monoclinic lattices ( a = 5.43 Å, b = 9.45 Å, c = 12.41 Å, and β = 90°), respectively, where all three adopt a nearly trans -conformation ( c = 12.41–12.65 Å) independent of stereoregularity . Moreover, Kafle et al reported that (i) s - and i -hPNBs are fixed crystals, while a -hPNB conducts large amplitude motions associated with a crystal–crystal transition into the rotator phase (mobile crystal) at T cc = 115 °C, and (ii) a -hPNB shows a much higher crystallinity (Φ c = 82%) and a much longer long period ( L = 80 nm) than those for stereoregular ones (Φ c = 50–55% and L = 17–21 nm) .…”
mentioning
confidence: 99%
“…13 C CSA spectra for (b, c) C7 and (d, e) C1,4 signals for pure a - (red) and s -hPNBs (blue) and their blend (green) measured by using SUPER at 25 and 123 °C and (b, c) simulated CSA patterns (dashed lines) for pure a - (red) and s -hPNBs (blue) and the blend (green). (b) Chain conformation for pure a - and s -hPNBs determined in ref and their dynamic models with orientations for the CSA principle axes on the C7 carbon …”
mentioning
confidence: 99%